Posthumanism explorations in Japanese folklore from selected stories in Japanese Folktales: Classic Stories from Japan’s Enchanted Past by Yei Theodora Ozaki and Japanese Legends and Folklore by A. B. Mitford - Chong, Siew Wen (2025)
This study aims to explore the animal, human-animal relationship from few selected stories in Japanese folklore by focusing on two animals which are sparrow and monkey. By analyse these animals, posthumanism theory by Cary Wolfe (2010) will be utilised to adapt in this study to challenge the human-centred concept in order to redefines that human is not the centre of the world through animal and human-animal relationship aspects to bring out the result to emphasis the concept of posthumanism is well-matched in this study. By using qualitative textual analysis in this study from two Japanese folklore book by Yei Theodora Ozaki (2018) and A.B. Mitford (2020), it bring out the main focus on animals as the characters in the selected stories play an crucial role to foster the animal status and their relationship with human through their characteristics and impact that contribute to this study. Hence, through the lens of using posthumanism theory into the sparrow and monkey in the selected stories is to establish animal is not as a tool for human and they are interconnected with human and form the relationship with them in the world. Overall, this study illustrates that Japanese folklore provides an impactful impact to be analyse by its animals in the selected which are rich in various aspects that is suitable to be using for examining and result in the outcome such as ethical, cultural and ecological aspects which are credible and insightful.